Peranan Hukum Sebagai Social Control dalam Pelaksanaan Demokrasi di Indonesia - Riyanto Riyanto (AL-BURHAN, 2023)
The rolling of the new order to the reform order, which began with the resignation of Soeharto President, democracy in Indonesia is slowly starting to appear, feeling depressed and pressured began to gradually eroded. The public is free to express their opinion, of course, within the limits set out in the applicable regulations. But often the freedom that society has is misinterpreted as unlimited freedom so that the result is anarchic acts. at will without regard to the rule of law. Therefore, other strategies and roles are needed for its implementation, one of which is with the implementation of legal functions as social control. Method of this research uses normative juridical approach by collecting the data, observations, and analyzing qualitatively, meanwhile normative is choosen because this study is a library research. and the processing of further data collected will be analyzed through three stages, they are selecting data, presenting data, and drawing conclusion of activity continuous, then it is repeated to form a cycle that allows generating sufficient final conclusion. The Functions of law sosiologiy as a social control is hopped can make society obedient to behavior law, because law goals to give benefit to society, so the role of law sosiology above goals to make society obedient to rule of law.